The effect of Gibberellin (GA3) concentration on flower loss and yield in the soybean (Glycine Max (L.) Merril) Anjasmoro Cultivar - Azzahra, Nabila; Aryono, Angela Dwi; Awaliyah, Salsa Rizki; Faqih, Achmad (Indonesian Journal of Multidisciplinary Science, 2025)
Soybean (Glycine max (L.) Merril) is one of the main crops widely grown around the world and can affect various aspects of the ecosystem. One of the efforts to increase soybean production and prevent flower loss is the use of plant growth regulators (PGRs). The purpose of this research is to reduce flower loss and increase production yields in the Anjasmoro cultivar of soybean plants. This study aims to: (1) determine the significant influence of gibberellin (GA3) concentration on flower shedding, the number of pods per plant, the dry pod weight (per plant (g) and per plot (g), and the dry seed weight (pt)) of soybean. The study was carried out at Beberan Village, Palimanan District, Cirebon Regency, Indonesia. The research used Randomized Group Design (RGD) with one treatment factor and 4 replications. The results showed that the concentration of gibbelliin (GA3) significantly influenced flower loss (p0.05) and yield (p>0.05). The application of 100 ppm (N2) of GA3 can produce the highest dry weight of 901.25 g/plot or 2,815.625 kg/ha and is significantly different from other treatments. In addition, the study identified the optimal concentration that minimizes flower loss while maximizing production yield under non-stress conditions, contributing valuable insights to enhance agricultural practices aimed at improving soybean productivity in Indonesia.